2014
DOI: 10.1039/c3ra45910a
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the dual role of the cholinium hexanoate ionic liquid as solvent and catalyst in suberin depolymerisation

Abstract: Disruption of the three-dimensional network of suberin in cork by cholinium hexanoate leads to its efficient and selective isolation. The reaction mechanism, which likely involves selective cleavage of some intermonomeric bonds in suberin, was still unanswered. To address this question, the role of the ionic liquid during suberin depolymerisation and during cleavage of standard compounds carrying key chemical functionalities was herein investigated. A clear demonstration that the ionic liquid catalyses the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 52 publications
2
45
3
Order By: Relevance
“…It was reported that lignin dissolution in ILs generally accompanied its structural modifications such as the cleavage of β‐O‐4 bonds, in which the IL anions played a primary role (George et al, ). Therefore, multiple functional groups in the anions may exert antagonistic effects on the dissolution of lignin, in which the ILs act as the dual roles of solvents and catalysts (Ferreira et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that lignin dissolution in ILs generally accompanied its structural modifications such as the cleavage of β‐O‐4 bonds, in which the IL anions played a primary role (George et al, ). Therefore, multiple functional groups in the anions may exert antagonistic effects on the dissolution of lignin, in which the ILs act as the dual roles of solvents and catalysts (Ferreira et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…trees harvesting (outer bark) (Pinto et al, 2009 ). In the perspective of its industrial use, the extraction of suberin from the suberized matrices has been made by conventional hydrolytic means, and more recently, was achieved using ionic liquids, specifically targeting the acylglycerol linkages (Ferreira et al, 2014 ).…”
Section: The Chemical Singularity Of Suberin Makes It Valuable For Inmentioning
confidence: 99%
“…Sodium alkyl-benzene sulfonates and sodium butyl monoglycolsulfate (NaBMGS) are used to extract non-polar, water insoluble phyto-constituents selectively due to permeabilization of the cell. Also choline hexanoate is able to dissolve suberin out of cork by cleavage of the ester bonds in suberin [14]. …”
Section: Introductionmentioning
confidence: 99%